The Differences of Individual Characteristics and Working Environment That Influence Job Stress on Female and Male Workers at Pt. X Sidoarjo (Using Gender Prespective) - Adli Prasetyo1, Tri Martiana2, Rr. Soenarnatalina Melaniani2 , Firman Suryadi Rahman3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Job stress can be defined as a dangerous physical and emotional response that occurs when work requirements are not matched with our own ability, resources, or needs of the workers. Job stress needs special attention by the company because it relates a worker individual’s health and affects operational continuity of the company’s production. The risk factors as the cause of job stress on female and male workers in PT. X are related to the characteristics and the perceptions of a work environment. The purpose of this research is to examine the individual characteristics and perceptions of the working environment that affects the incidence of job stress on female and male workers. This type of research is observational by designing cross-sectional research with the number of respondents as many as 50 people. The independent variables in this study included age, education, employment, marital status, noise, lighting as well as temperature. Dependent variable was job stress on female and male workers in PT. X. Female workers at PT. X experienced 32% of job stress and 20% of male workers. The results of logistic regression analysis obtains a significant influence of working time with job stress (P=0.027) as well as noise with job stress (P=0.017) on female workers. Male workers are significant to the job stress namely age (P=0.011), working period (P=0.030) as well as lighting (P=0.005). Advice for job-stress workers to take a leave, using personal protective equipment to reduce the risk of working environment. The company provides leave permits for workers and periodically performs work rotation.